Is it necessary to describe the instruments used in empirical research? - Calderón de la Cruz, Gustavo Alexis (2016)
In the recent publication of Izaguirre-Sotomayor et al. (1), the authors report the use of a scale to assess attitudes towards ethics, but in the 'Methods' section, the description of the instrument is limited because no information on the process of obtaining evidence of validity is reported, estimates reliability and scales of scores. The absence of this information does not reveal if the scale in question meets the requirements requested by the international quality standards of a test, specifically regulatory and psychometric criteria that constitute it and the effects of use (2).